Effects of core muscles strengthening exercises with routine physical therapy on trunk balance in stroke patients: a randomized controlled trial - Nadeem, Iqra; Butt, Sara Khawar; Mubeen, Iqra; Razzaq, Ayesha (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the effects of core muscle strengthening exercises with and without routine physical therapy on trunk balance in chronic stroke patients. Method: The randomised controlled trial was conducted at Mubarak Medical Complex, Sargodha, Pakistan, from October 28, 2021, to April 28, 2022, and comprised patients of either gender with chronic stroke aged 40-60 years. The subjects were randomised using the lottery method into group A that was managed with routine physical therapy, and group B which was further managed with core strengthening exercises. The intervention comprised 4 sessions per week for 8 weeks. Outcome was measured using Trunk Impairment Scale and Time Up and Go test. Data was collected at baseline, week 4 and post-intervention. Data was analysed using SPSS 23. Results: Of the 80 individuals screened, 74(92.5%) were included. There were 37(50%) patients in group A; 30(81%) males and 7(19%) females with mean age 56.73±2.37 years. The remaining 37(50%) patients were in group B; 27(73%) males and 10(27%) females with mean age 55.65±2.88 years. Trunk balance and functional mobility improved significantly post-intervention in both groups (p<0.05), but group B values were significantly better compared to group A values (p<0.05). Conclusion: Core muscle strengthening exercises combined with routine physical therapy were found to be more effective compared to routine physical therapy alone in chronic stroke patients for improving trunk balance and functional mobility. Registration Number: IRCT20211116053070N1. Key Words: Stroke, Cerebrovascular accident, Muscle strengthening exercise, Physical therapy, Trunk balance, Functional mobility.